Donating Food to a Monastery: Gift and Communication - Laužikas, Rimvydas (History / Istorija, 2025)
The article focuses on the study of food donations at the rural Dominican Monastery in Lithuania. The theoretical framework applied perceives donations not only as the transfer of goods but also as a process of information transmission. In this process, the donor is the sender of the message; the gift becomes the message; the act of giving is the channel of communication; and the recipient of the gift is the receiver of the message. The article presents the gastronomic culture of the Monastery and a classification of the possible communicative meanings of food donations. Gifts of care, gratitude, connection, and joy are identified in the Monastery’s donation book. According to the donation book, these donations differ in terms of the types of food donated, the frequency of donations, and the social profiles of the donors.